Efektivitas Penertiban Pedagang Kaki Lima di Kota Bukittinggi - Ichwanul Muslimin. Sy; Mayarni Mayarni (LPPM Politeknik Pratama, 2024)
Effectiveness is a measure of task results or success in achieving goals. The Civil Service Police Unit is a regional apparatus organization that has duties stand up rules area and organize peace and public order as well as community protection. Objective study this is to Identify and analyze effectiveness or dering street vendors below bridge fly over market Aur Kuning in the Bukittinggi city as well as identifying and analyzing inhibiting factors in controlling street vendors in the areas below bridge fly over Aur Kuning market, Bukittinggi City. Study Thisuse theory according to Mahmudi which uses 4 indicators, Input, Process,Output, Outcome. The research method used in this research uses descriptive qualitative methods and data collection techniques through primary and secondary data sources obtained through the process of observation, interviews and documentation by past researchers analyzed. Research resultshow control carried out by the civil service police unit against street vendors under the bridge fly over Aur Kuning market in the Bukittinggi city has not been effective because control is not carried out optimally from all aspects that influence the results of control.